Answer:
(-135)/4
Explanation:
Evaluate -(3 x^2)/4 - 2 x^2 + x - 12 where x = 3:
-(3 x^2)/4 - 2 x^2 + x - 12 = 3 - 2×3^2 - 3/4×3^2 - 12
3^2 = 9:
3 - 29 - 3/4×3^2 - 12
3^2 = 9:
3 - 2×9 - 3/4×9 - 12
-2×9 = -18:
3 + -18 - 3/4×9 - 12
-3×9 = -27:
3 - 18 + (-27)/4 - 12
Put 3 - 18 - 27/4 - 12 over the common denominator 4. 3 - 18 - 27/4 - 12 = (4×3)/4 + (4 (-18))/4 - 27/4 + (4 (-12))/4:
(4×3)/4 - (18×4)/4 - 27/4 - (12×4)/4
4×3 = 12:
12/4 - (18×4)/4 - 27/4 - (12×4)/4
4 (-18) = -72:
12/4 + (-72)/4 - 27/4 - (12×4)/4
4 (-12) = -48:
12/4 - 72/4 - 27/4 + (-48)/4
12/4 - 72/4 - 27/4 - 48/4 = (12 - 72 - 27 - 48)/4:
(12 - 72 - 27 - 48)/4
12 - 72 - 27 - 48 = 12 - (72 + 27 + 48):
(12 - (72 + 27 + 48))/4
| 1 |
| 7 | 2
| 4 | 8
+ | 2 | 7
1 | 4 | 7:
(12 - 147)/4
12 - 147 = -(147 - 12):
(-(147 - 12))/4
| 1 | 4 | 7
- | | 1 | 2
| 1 | 3 | 5:
Answer: (-135)/4